Hydrogen Peroxide Induced Colitis: A Case Report and Literature Review - Dushyant Pawar; Anna Calara; Roy Jacob; Nancy Beck; Alan N. Peiris (Case Reports in Gastrointestinal Medicine)
Constipation is a common condition. Hydrogen peroxide enemas have rarely been reported as a home remedy for constipation in the pediatric age group. We present a case report and literature review of hydrogen peroxide induced colitis in pediatric siblings, aged 2 years and 9 years. The siblings presented with vomiting and bloody diarrhea an hour following the enema. Physical exam, vital signs, blood, and electrolyte counts were normal, but CT scans showed mucosal thickening of the rectum and colon. Their symptoms resolved after oral intake was curtailed and fluids were replaced intravenously. We discuss existing reports of complications from hydrogen peroxide enemas. Patients may present with abdominal pain and bloody diarrhea. Onset of symptoms varied from minutes to a day and bowel ulceration with necrosis and perforation has occurred, although fatality is rare. Diagnostic tests included computed tomography (CT) scan, sigmoidoscopy, or biopsy. Recovery period ranged from 3 days to 8 months. Public education regarding the dangers of hydrogen peroxide enemas is needed.